Implementation of Discovery Model Assisted by Flipbook Media on Learning to Write Poetry Text - Jaenudin Jaenudin; Enung Nurhayati; Via Nugraha (IKIP Siliwangi, 2023)
In the preliminary survey that has been conducted in the classroom, students have the value of poetry writing skills under the minimum completeness criteria that have been set by the school. The background of this study is the low ability to write poetry texts of Junior High School students. Students ' ability to write poetry texts needs to be improved because students must be trained in pouring words with imagination in the surrounding environment. This study aims to determine the effectiveness of the discovery learning learning model with the help of flipbook media, the results of writing poetry texts after the implementation of the learning model and the activities of teachers and students during the learning process. This study uses a qualitative approach with descriptive analysis techniques. The Data were obtained based on the results of the application of the discovery learning learning model assisted by flipbook media which can improve the writing skills of Al Inayah Kutamukti Junior High School students. The presentation includes: 1) learning syntax, 2) the results of students ' poetry writing skills, and 3) the results of observations of teacher and student activities. The data obtained in this study are presented in Tabular Form and analyzed descriptively. The data processing is done by researchers, namely display, reduction and conclusions. The results of descriptive analysis after the first application, the steps of learning to write poetry texts using the discovery learning method assisted by flipbook media, namely the provision of stimuli or stimuli with flipbook media. 2) identify problems on how to write poetry 3) collect data from several sources facilitated by teachers 4) process information 5) proof and 5) draw conclusions. Second, the value of students in writing poetry obtained an average of 82 with the lowest value of 79 and the highest 86. The Data showed that the results of writing poetry students have reached the minimum criteria of completeness is 75. Then the last activity of teachers and students in the learning process based on the observation of 88% which means it has a good category. These results can be concluded that the learning model of discovery learning assisted by flipbook media is effective for learning to write poetry.